2022
DOI: 10.3390/foods11162518
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Common Vegetables Inhibit the Growth of Ovary Cancer Cells

Abstract: There is recent interest in a diet that can be recommended for patients suffering from cancer. In this respect, the effects were studied of the extracts of several common fruits, herbs and vegetables on the viability of two human ovary cancer cell lines (SKOV-3 and PEO1) in vitro. Normal human MRC-5 fibroblasts were used as a control cell line. The extracts of garlic, horseradish and curly kale as well as green and black tea were the most effective in lowering the viability of ovarian cancer cells, while not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…The strong inhibition of the proliferation of PEO1 cells by PBS extracts of fresh Spanish garlic is in general agreement with the results of our previous study [ 56 ] in which such extracts were used. We found previously 50% inhibition of the proliferation of PEO1 cells by a PBS extract from Spanish garlic at a concentration corresponding to 0.31 μg extract/100 μL (using a different batch of garlic).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The strong inhibition of the proliferation of PEO1 cells by PBS extracts of fresh Spanish garlic is in general agreement with the results of our previous study [ 56 ] in which such extracts were used. We found previously 50% inhibition of the proliferation of PEO1 cells by a PBS extract from Spanish garlic at a concentration corresponding to 0.31 μg extract/100 μL (using a different batch of garlic).…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the effects of extracts of various fruits and vegetables on the proliferation of ovarian cancer cells, we found an exceptional antiproliferation ability of aqueous garlic extracts. The proliferation of PEO1 and SKOV3 ovarian cancer cells was 50% inhibited by extracts from 1.11 and 3.33 μg of garlic per 100 μL medium, respectively [ 56 ]. The aim of the present study was to examine how this antiproliferative activity of garlic extracts varies within various garlic cultivars and preparations available commercially, and how it depends on the solvent used for extraction.…”
Section: Introductionmentioning
confidence: 99%
“…There is only rare evidence of anticancer activity of wild Brassica species [ 6 ] and flat-leaved kale [ 36 , 47 ]. Although glucosinolates are mostly reported as bioactive molecules with anticancer activity [ 24 , 25 ], Furdak et al [ 51 ] showed that the cytotoxic effects of a number of plant extracts, including white cabbage extracts, also correlated with their polyphenol content. Sinapic acid and ferulic acid, found at a high level in Brassica species, are strong antioxidants with reported anticancer activity [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Garlic ( Allium sativum L.) is a traditional food grown worldwide, both as a flavoring and medicinal food [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], with a harvested area of 1.63 million hectares worldwide [ 8 ]. Currently, the harvesting and post-processing of garlic in China are primarily carried out manually, which is labor-intensive and inefficient.…”
Section: Introductionmentioning
confidence: 99%